Aortic Arch. The Final Frontier in Cardiac Surgery - Dimos Karangelis; Apostolos Roubelakis; Dimitris Mikroulis; Matthew Panagiotou (Journal of Investigative Surgery, 2019)
Aortic arch pathologies such as acute aortic dissection and aneurysmal disease represent surgical challenges. Various emerging techniques and surgical prostheses have expanded the therapeutic armamentarium over the last years with one principal objective; to simplify the operation and reduce the surgical time. Besides the classic elephant trunk which has been regarded as an evolutionary leap in the treatment of extensive thoracic disease, other novel surgical approaches such as the frozen elephant trunk, the thoracic endovascular aortic repair (TEVAR) and the hybrid open branched stent grafts have been introduced. This brief review aims to evaluate the surgical alternatives used in the management of complex aortic arch and proximal descending aorta pathologies with particular consideration given to the contemporary approaches which endorse single stage operation.